PERCEPTION OF STUDENTS AND TEACHERS ABOUT DIDECTIC TEACHING AMONG PUBLIC AND PRIVATE COLLEGES - BIBI, M; SADDIQUE, H; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Didactic teaching remains the dominant pedagogical approach in many educational institutions worldwide, including Pakistan. This study aimed to assess and compare the perceptions of students and teachers regarding didactic teaching in public and private colleges in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted from January to July 2024, involving 152 participants (95 students and 57 teachers) from public and private colleges in Lahore. Participants were selected using stratified random sampling. Data were collected through a structured, pre-tested questionnaire assessing demographic characteristics, perceptions of didactic teaching, and preferences for interactive teaching methods. The data were analyzed using SPSS version 26.0. Chi-square and t-tests were employed to compare perceptions between groups, with statistical significance set at p < 0.05. Results: The majority of teachers (68.4%) favored didactic teaching, particularly for syllabus coverage in limited timeframes. In contrast, only 42.1% of students found didactic teaching effective, with significant differences between public (54%) and private (36.4%) college students (p < 0.05). Furthermore, 70.5% of students preferred interactive teaching methods such as group discussions and problem-solving activities, compared to 36.8% of teachers (p < 0.05). Private college participants, both students and teachers, showed a higher preference for interactive methods compared to their public counterparts (p < 0.05). Conclusion: This study highlights a significant divide between students’ and teachers’ perceptions of didactic teaching in public and private colleges. While teachers, particularly in public colleges, defend didactic teaching as efficient, students, especially in private colleges, express a clear preference for interactive methods. These findings suggest the need for reforms in Pakistan’s higher education system to integrate more interactive teaching approaches while maintaining the efficiency of didactic methods, especially in public institutions.